Effect of Brand Image, Education Cost, and Education Facilities on Student’s Decision in Choosing Accounting Department (Dinamika Pendidikan, 2017)
This research aims to know the illustration of brand image, education cost, and education facilities related to the student’s decision in choosing the Accounting Department, Faculty of Teacher Training of Universitas Islam Riau. This research was conducted in August 2016. The subject in this research is the students of FKIP Accounting Department of Universitas Islam Riau, semester 3, 5 and 7 with a population of 318 students. 177 students were analyzed as sample. The technique of research used random sampling and method used descriptive quantitative. The data of brand image, education costs, education facilities, and student’s decisions are obtained from questionnaires. Multiple linear regressions were used to analyse the data and the calculation of coefficient determinant (R) was used to know the influence of brand image, education cost, and education facilities.